The Value and Significance of Rowing in Colleges and Universities - Li, Du (Journal of Theory and Practice of Contemporary Education, 2023)
Modern rowing is the perfect representation of human physical ability and intelligence, and its core cultural essence is the pursuit of harmony between man and nature and the spirit of active struggle. Campus rowing has developed rapidly in China, but it is still in its infancy. To ensure the scientific degree and healthy growth of campus rowing training requires efforts from various aspects. Rowing in colleges and universities has a broad prospect, plays an important role in the cultivation of the two major curriculum objectives of mental health and social adaptability, is a new supplement to traditional sports teaching, and is of great significance in promoting the reform of the traditional education model and improving the overall quality of college students.